Impactos ambientales ocasionados en la superficie boscosa por ampliación y asfaltado de la vía panamericana, parroquia Casanga, cantón Paltas, provincia de Loja - Ambuludi Gómez, María Alejandra (2019)
The Environmental Impact Assessment today is one of the most effective methods to prevent environmental aggression, conserve and recover natural resources in the realization of projects for the good of communities and thus maintain biodiversity and conserving ecosystems. For this reason, a study was carried out in this research on the environmental impacts that occur on the forested area caused by the expansion and asphalt of the Pan American way, in the section that begins from the crossing of the pan-American that leads to the Celica and Macará border cantons (km 68 E35) towards the center of the village Casanga in an area of 3.15 km. The study area is located to the south west of the canton Paltas, 26 km from the Cantonal Catacocha. The methodology used allowed information on the floristic composition of two study areas (Referential Zone and Condition Zone), in each area four transects of 2 500 m2 (10 000 m2 of the total sampling area) were installed that allowed to evaluate their conservation status; In addition, changes in plant cover, floristic composition and soil seed bank were analyzed as potential direct impacts caused by the widening of the track. The results show that the reference area has the largest number of families, species and individuals compared to the condition zone. Among the main botanical families is characterized the presence of species belonging to the Fabaceae, which is found in both study areas, while the Apocynaceae family is characterized by being present only in the area of condition. With regard to the change in plant cover and land use over an 18-year period, a 20 % change in most land uses is evident. The alteration of the floristic composition of the assessed areas is shown, as there are species that prefer a certain area to develop, the Sorensen similarity coefficient shows that they share 31,58 %, so these are two sites medium-like what is checked with the cluster analysis performed. In the soil seed bank, the germination of species that grow in a certain area is evidenced so it can be attributed to a direct impact of the pathway. The identified impacts will allow decision makers to generate environmental strategies that contribute to the conservation of the biodiversity of the dry forests of the Casanga parish. Key words: Dry forest, floristic composition, seed bank, regeneration, coverage and land use, environmental impact, GIS.